Mechanical Properties of Polypropylene Biocomposites Reinforced with Man-Made Cellulose Fibres and Cellulose Microfibres. (April 2019) - Japins, Guntis; Franciszczak, Piotr; Kalnins, Kaspars; Kovalovs, Andrejs
Abstract: This paper presents the influence of man-made cellulose fibres and cellulose microfibres on the mechanical properties of reinforced composites based on polypropylene matrix. The hybrid combination of these reinforcements was also used. The man-made cellulose fibres and cellulose microfibres were compounded with polypropylene. The volume fractions of reinforcement and compatibiliser were maintained at the proportional levels to enable correlation of mechanical properties. The manufactured composite compounds were subsequently injection moulded into testing specimens. Mechanical properties such as tensile and flexural strength, tensile and flexural modulus were determined. The data obtained from experiments have shown that addition of the cellulose fibres and microfibres to the polypropylene matrix has reinforcing effect on its tensile and flexural properties, which depends mostly on volume fraction of reinforcement and its type. The hybrid combination has shown higher than expected properties, especially at higher volume fractions.